A critical analysis of the earnings management strategies in politically influenced firms. (10th February 2023) - Sadiq, Muhammad; Othman, Zaleha; Keong, Ooi Chee
The purpose of this paper is to investigate whether politically influenced firms employ income-decreasing accrual-based earnings management strategy to report less taxable income. The current study also investigates whether politically influenced firms substitute one of the earnings management strategies with the other. The study analysed data from 290 firms listed in Pakistan Stock Exchange over the nine years period. The results envisaged that politically influenced firms manipulate earnings downwards with the objective to report less taxable income, pursuant to which the regulators must keep political factors in mind during regulatory reforms. This study also found that politically influenced firms substitute one earnings management strategy with the other. This study contributes to the field of earnings management where it integrates agency theory with political economy theory. The paper suggests that downwards accrual-based earnings management strategy is the underlying mechanism through which politically influenced firms report less taxable income. The paper contributes to the field of corporate governance study where we provide deep insight to policymakers who are interested in improving corporate governance in transnational economies.